DISIPLIN KERJA GURU YANG TELAH DISERTIFIKASI DALAM MELAKSANAKAN TUGASNYA DI SEKOLAH MENENGAH ATAS NEGERI KECAMATAN PAUH PADANG - Adek Febriyanti (Universitas Negeri Padang, 2014)
The goal of this research are to see information about certification teacher’s discipline in doing his duty. The population is 110 people and the sample is 86 people that taken by Krejcie. The instrument of this research is question with Likert scale models that had tested for validity and reliability. Data analyzed using mean score . The result of this research are the certification teacher’s discipline in doing his duty at high school Negeri Kecamatan Pauh Padang stay in quite accomplished category. Key word : Certification teacher’s discipline in doing his duty